EVALUATION OF THE INDONESIAN GOVERNMENT'S BUDGET EFFICIENCY POLICY INTERVENTION IN 2020: FROM THE PERSPECTIVE OF THE FINANCIAL PERFORMANCE OF THE TRANSPORTATION AND HOSPITALITY SECTOR - Palenteng, Vanesa Claudia; Worang, Frederik Gerdi; Tasik, Hizkia H.D. (Jurnal Manajemen, 2026)
Abstract: The Indonesian government's budget efficiency policy in 2020, through refocusing and reallocation of spending, aimed to maintain fiscal stability amid the Covid-19 crisis. However, this intervention had direct implications for the transportation and hospitality sectors, which are highly dependent on public mobility and tourism. This study evaluates the financial performance of companies from these two sectors listed on the Indonesia Stock Exchange during the 2018–2023 period, using the Interrupted Time Series Analysis (ITSA) method to assess profitability indicators. The results show a decline in Operating Profit Margin (OPM) after the policy was implemented, reflecting operational pressures due to declining demand. Conversely, Net Profit Margin (NPM) and Return on Assets (ROA) did not experience significant changes, indicating that the policy's impact was more pressing on operating margins than on net profitability and asset utilization efficiency. These findings confirm the differential effects of fiscal consolidation on corporate financial performance and provide new evidence from the Indonesian services sector in the context of policy interventions during the Covid-19 crisis.Keywords: Budget Efficiency, Profitability, Hospitality, Transportation, ITSA